20 pointsA large amount of peanuts was divided equally into 6 small bags. The total number of peanuts, p, was 342. Which
statements can be used to write an expression and then find the number of peanuts that ended up in each bag?
Check all that apply.
The operation is division.
The operation is multiplication.
The variable is the number of bags.
342 divided by 6 equals 57.
Write the division expression as a fraction,
To evaluate, substitute 342 for the variable.
Each bag will have 57 peanuts.
The constant is 342.

Answers

Answer 1
Answer:

Answer:

I think the answer is A, D, E, F, and G.

Tell me if i'm right or wrong please.

Answer 2
Answer:

Answer:

adefg

Step-by-step explanation:


Related Questions

1) In 2001, there were about 62.5 thousand golden retrievers registered in the United States. In 2002, the number was 56.1 thousand. Which linear equation best represents this information?(A) y = 6.4x + 2001 (B) y = -6.4x + 12868.9 (C) y = 6.4x - 12743.9 (D) y = -6.4x + 2002
Laurie is trying to stay within 10 feet of her current diving depth of –30 feet (with regard to sea level) so that the light is still good but she can be close to the sea life during her scuba dive. Which two equations can be used to find the minimum and maximum depths Laurie wants to stay between?A. x + 30 = 10 and x + 30 = –10 B. x – 30 = 10 and x – 30 = –10 C. x + 10 = 30 and x + 10 = –30 D. x – 10 = 30 and x – 10 = –30
Two cards are randomly selected, without replacement, from a standard deck of playing cards. What is the probability of first picking a five and then picking a card other than a five? I'm having a time with determining which formula to use?
17.16 is 62.4% of what
Find the value of p(-1)=4x^4+5x^3-x^2+6

(5+2yi)(4-3i) - (5-2yi)(4-3i) in a + bi form, where y is a real number.

Answers

(5+2yi)(4-3i) - (5-2yi)(4-3i)

Factorize out (4 - 3i)

(4 -3i)( (5 + 2yi) - (5 -2yi) )

(4 -3i)(5 + 2yi - 5 + 2yi)

(4 -3i)(5 - 5 + 2yi + 2yi)

(4 -3i)4yi

4*4yi - 4yi*3i

= 16yi - 12yi².                 i² = -1

=
16yi - 12y(-1)

= 16yi + 12y

= 12y + 16yi                in the form a + bi.
(5+2yi)(4-3i) - (5-2yi)(4-3i)=\n(4-3i)(5+2yi-5+2yi)=\n(4-3i)\cdot4yi=\n16yi+12y=\n12y+16yi

Can someone help me with this triangle??
Find missing side lengths

Answers

Answer:

M= 15 degrees    N= 15 degrees

Step-by-step explanation:

Right triangles are always 90 degrees so 90-60=30

since theres 2 sides you have to split 30 in 2 so 30 divided by 2 equals 15

Write 9(39) using the Distributive Property. Then simplify.

Answers

9 x 3 = 27
9 x 9 = 81
27+81= 109

Simplify. Write each answer in scientific notation. 15. (6 ˣ 10^-5)^3
19. 3 ˣ 10^-2 / 8 ˣ 10^-1
20. 4.1 ˣ 10^-4 / 1.28 ˣ 10^-5
21. 1.91 ˣ 10^3 / 5 ˣ 10^-4

Answers

Scientific notation is always supposed to be

                 (a number between 1 and 10)  x 10^whatever power.


15.  (6 x 10⁻⁵)³

The 'cube' works on everything inside the parentheses ...
the 6 and the 10⁻⁵ .

So this thing is  (6)³ x (10⁻⁵)³  .

That's          (216) x (10⁻¹⁵) .  After cleaning up, it's  2.16 x 10⁻¹³ .

19.    3 ˣ 10⁻²  /  8 ˣ 10⁻¹

This mess can be written in a slightly different way,
and it may be clearer to you that way:

            (3/8)  x  (10⁻²/10⁻¹)

The 3/8 is 0.375 .
The second factor is    10⁻¹ .

So we have  0.375 x 10⁻¹ .  After cleanup, it's  3.75 x 10⁻² .

20. 4.1 ˣ 10⁻⁴ / 1.28 ˣ 10⁻⁵

Write it like this:  (4.1/1.28) x (10⁻⁴/10⁻⁵)

The first part is 4.1/1.28 = 3.203125 .

The second part is  (10⁻⁴/10⁻⁵) = 10¹

So it boils down to       3.203125 x 10¹ .

 21.  1.91 ˣ 10³ / 5 ˣ 10⁻⁴

Write it like this:       (1.91/5)  x  (10³/10⁻⁴)

First part:  1.91/5 = 0.382

Second part:   (10³/10⁻⁴)  =  10⁷

Put um together:  0.382 x 10⁷ .  After cleanup:  3.82 x 10⁶ .

What is the first step when rewriting y = –4x2 + 2x – 7 in the form y = a(x – h)2 + k?A.2 must be factored from 2x – 7

B.–4 must be factored from –4x2 + 2x

C.x must be factored from –4x2 + 2x

D.–4 must be factored from –4x2 – 7

Answers

complete the square

first, the coeieicne infront of x^2 term musbe 1
so if you have
y=ax^2+bx+c
isolate x terms and undistribute a
y=a(x^2+(b/a)x)+c

B is answer

Answer:

B

Step-by-step explanation:

Right on Edge

Cedric and doug each had an equal amount of money. After cedric spent $35 and doug spent $28, the ratio of cedrics money to dougs money was 2:3. How much money did each boy habe at first?

Answers

Answer:

Each of them had $49 at first.

Step-by-step explanation:

Given:

Cedric and Doug each had an equal amount of money.

Let the number of money they had at first be x

Cedric spent = $35

Doug spent = $28

Cedric Money left = x-35

Doug Money left = x-28

the ratio of Cedric money to Doug money was 2:3

Hence the expression can be made as;

(x-35)/(x-28)=(2)/(3)

Now by cross multiplication method we get;

3(x-35)=2(x-28)

Now we will use distributive property to elaborate the same;

3x-105=2x-56

Combining common terms we get;

3x-2x=105-56

Using Subtraction property we get;

x= 49

Hence $49 they each had at first.